The tourist function in a car factory Audi Forum Ingolstadt example - Cudny, Waldemar; Horňák, Marcel (Bulletin of Geography. Socio-economic Series, 2016)
The article presents modern car industry and tourism issues. It is a case study of a multifunctional centre - the Audi Forum Ingolstadt, situated next to a large Audi factory in Ingolstadt, Germany. It was created in order to promote the Audi brand and provide service for the customers picking up their cars in Ingolstadt. It also performs tourist functions as it focuses on providing service for the people who arrive to visit the car factory, the Audi museum mobile and the region. The centre offers specific tourist products based on particular experiences, which may be included in industrial tourism. The facilities in the Audi Forum Ingolstadt are tourist assets in themselves; they may also be seen as tourist infrastructure. It is also a place where numerous events are held, attracting tourists. The Audi Forum Ingolstadt is an example of a multifunctional centre with distinctive tourist functions, situated on the premises of a large modern car factory.